Morphological and Chemical Properties of Particulate Matter in the Dammam Metropolitan Region: Dhahran, Khobar, and Dammam, Saudi Arabia - Bassam S. Tawabini; Taoreed T. Lawal; Abdulaziz Shaibani; Ashraf M. Farahat (Advances in Meteorology)
Characteristics of airborne particulate matter (PM) as well as its levels in air samples collected from selected sites within cities of Dhahran, Khobar, and Dammam, in the Eastern Province of Saudi Arabia, are investigated. Concentration levels of the 10 microns’ PM (i.e., PM10) are determined using the gravimetric technique. Morphological and chemical characteristics of the PM collected from the sampling cities are studied using Field-Emission Scanning Electron Microscopy (FESEM), energy dispersive X-ray (EDX), and X-Ray Fluorescence (XRF). Moreover, levels and types of hazardous materials related to these samples are assessed using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). Results revealed that the average concentration levels of PM10 were approximately 177, 380, and 126 μg/m3 in Dhahran, Khobar, and Dammam, respectively. The structure of PM collected in Dhahran was mainly platy and rod-like shaped with a size between 2 and 6 μm, while PM collected in Khobar was mostly irregular in form, with a size range between 2 and 8 μm, and Dammam’s PM was rounded and between 1 and 3 μm in size. Both EDX and XRF results indicate relatively high weight % of C, O, Si, F, and Ca with lower weight % of Na, Mg, and K at the 3 cities. Finally, the study shows that Ba and Zn were the main trace metals associated with the collected PM in the 3 cities.